1970
DOI: 10.1126/science.170.3965.1418
|View full text |Cite
|
Sign up to set email alerts
|

Tongue Cooling: A New Reward for Thirsty Rodents

Abstract: Thirsty rodents will persistently lick a stream of dry air pumped through a standard drinking tube. This air-licking is attenuated by experimental manipulations which reduce the evaporative cooling of the tongue and mouth produced by the airstream. This suggests that such cooling is itself an effective reward for thirstry rodents. We tested this hypothesis by presenting thirsty rodents with a piece of cold, dry metal. Different species spent from 9 to 40 percent of their session time licking the cold metal. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…Once again, this behavior appeared to resemble scheduleinduced licking of the dry tube. Mendelson and Chillag (1970) reported that schedule-induced licking occurred when a cold closed stainless steel drinking tube was made available. The stainless steel water tube in the present study apparently assumed the same function.…”
Section: Drinking Contrast R-op3mentioning
confidence: 99%
“…Once again, this behavior appeared to resemble scheduleinduced licking of the dry tube. Mendelson and Chillag (1970) reported that schedule-induced licking occurred when a cold closed stainless steel drinking tube was made available. The stainless steel water tube in the present study apparently assumed the same function.…”
Section: Drinking Contrast R-op3mentioning
confidence: 99%
“…Cold water reduces water intake during the short (less than 30 sec) bursts of drinking that occur on intermittent schedules of food reinforcement (Carlisle & Laudenslager, 1976). Similarly , the stomach clearance hypothesis does not explain why thirsty animals lick a cold, dry tube (Mendelson & Chillag , 1970) or air (Hendry & Rasche, 1961). These observations are consistent with the view that orolingual cooling alone has a satiating effect on thirst.…”
Section: Discussionmentioning
confidence: 55%
“…If preference for water of a particular temperature were based on the presumably innately determined intrinsic action of cold water on tongue receptors (Mendelson & Chillag, 1970;Kapatos & Gold, 1972;Bartoshuk, 1972), the results of Experiment I would be expected to have shown a clear and consistent preference for cooler water in all animals. However, only when the rats were allowed to choose between 36° and 12°C water was the preference decisive.…”
Section: Discussionmentioning
confidence: 97%